33 Hen. 8, ch. 6 (1541) - (:unkn) unknown (My University, 1541)
1, 2, 18: Prohibited possession of any crossbow, handgun, hagbutt, or demy hake. Exempted subjects living within 12 miles of the Scottish border. Punishable by forfeiture or payment of 10 pounds.
Keywords: POSSESSION